Conocimiento y práctica del enfermero sobre cuidado del catéter venoso central en pacientes de UCI pediátrica Hospital Regional de Loreto Iquitos 2025 - Cabudivo Flores, Melissa Magaly (2025)
The objective of this research is to determine the relationship that exists between the knowledge and practice of the nurse on central venous catheter care in pediatric ICU patients at the Regional Hospital of Loreto 2025. The type of research is quantitative and the design is Non-experimental, descriptive, correlational, cross-sectional, the population and sample will be made up of 55 nurses who work in the Pediatrics department of the Regional Hospital of Loreto in the year 2025. The technique will be the survey and observation, the The instruments will be the nurse's knowledge questionnaire on central venous catheter care and the central venous catheter care observation list. The data will be processed with the statistical software SPSS version 27.0, the chi square statistical test (χ²) will be used to examine the relationship between the variables, the level of significance will be 95%, with an alpha value (α) of 0.05.